(untitled) (Journal of Hama University, 2019)
This study aimed to compare mechanical properties of two kinds of coated orthodontic wires with or without immersing them in fluoride rinses. Two kinds of coated aesthetic wires were used (NiTi wires coated with Teflon and coated with composite 0.022*0.016 Inch). The specimens were divided into two groups: control group (wires without immersing in fluoride rinses) (20 wires coated with Teflon – 20 wires coated with composite) – and the other group (wires were immersed in fluoride rinses) (20 wires coated with Teflon – 20 wires coated with composite). The wires were cut into small pieces with the length 20 mm. Then, they were subjected to three-point bending test in the temperature 1 ± 37 in order to investigate their mechanical properties (Young modulus –– Tensile strength). According to the result of this study, there was a significant effect on the mechanical properties of coated wires (Teflon – Composite) after immersing them in fluoride rinses in which the yield strength, young modulus and tensile strength were less than those in the control group